Factors Affecting Consumers’ Conformity, Trust, and Purchase Intention in Live Streaming Shopping in Hangzhou, China - Xun, Jiang (Scholar: Human Sciences, 2025)
Purpose: This research paper investigates the factors affecting consumers’ conformity, trust, and purchase intention in live-streaming shopping in Hangzhou, China. The conceptual framework proposed a causal relationship among professionalism, price discounts, immersion, parasocial interaction, social presence, consumer conformity, trust, purchase intention. Research design, data, and methodology: The researcher applied the quantitative method (n=500), distributing questionnaires to residents in Hangzhou who were over 18 years old and had a live-streaming shopping experience. The Nonprobability sampling includes judgmental, quota, and convenience sampling in collecting data and distributing surveys online and offline. The Structural Equation Model (SEM) and Confirmatory Factor Analysis (CFA) were used for the data analysis, including model fit, reliability, and validity of the constructs. Results: The results explained that professionalism, price discounts, immersion, parasocial interaction, social presence, consumer conformity, and trust significantly impacted purchase intention. Professionalism and price discounts had a significant impact on trust. Trust presented the strongest effect on purchase intention, followed by immersion, social presence, consumer conformity, parasocial interaction, price discounts, and professionalism. Price discounts presented the strongest effect on trust, followed by professionalism. Conclusions: Live streaming companies and live streamers are suggested to make good use of the marketing channel of live streaming to enhance consumers’ purchase intention.